Notes on Procedural Speed in the New Peruvian Criminal Procedure Model - Villavicencio Rios, Fressia Sissy (2010)
The present paper analyzes one of the contributions of the new Peruvian criminal procedure model: procedural speed. The new norm must respect both the principle of celerity and the right to defense, and in that sense, it must harmonize both. The body in charge of speeding up the process is the Public Ministry, since it has the power to decide whether or not to initiate the process and determine the strategy to be followed: direct accusation, the immediate process, the process of early termination, among others. The author develops the analysis of procedural speed in the different stages of the process. In this sense, first, the materialization of the procedural speed during the preparatory investigation stage is analyzed. Concluding that currently the right to the reasonable term is violated, because, although the norm establishes maximum terms, these are not respected and, on the contrary, practices have proliferated that impede the procedural speed, such as, not to dictate a fiscal disposition to decide the police intervention and as a result the parties are not notified; likewise, it is observed that the prosecutors do not dictate any disposition with respect to the requests of term of term, as a result the judge of preparatory investigation must request a hearing for the control of this. Secondly, it is noted that during the processing of the tax requirements of restrictive measures of rights, the principle of procedural speed is respected, since this is resolved during the periods established by law. Similarly, the author analyzes, thirdly, the development of procedural speed during the immediate process and common process with immediate prisoner. In the immediate process it is appreciated that the investigating judge preparatory should review the fiscal folder in order to verify the assumptions that this invokes. The author concludes that with respect to this process procedural speed is respected. However, the same is not the case with regard to the common process, since normally, this does not respect the deadlines established in the standard. Finally, the materialization of procedural speed during the early termination process is analyzed. The author concludes that in these cases the rule hinders the procedural speed, because, for example, this can not be issued during the hearing process to control the tax accusation.